1999
DOI: 10.1088/0953-8984/11/15/019
|View full text |Cite
|
Sign up to set email alerts
|

Transport and magnetic properties in perovskite compound

Abstract: Magnetic and transport properties of the series (x = 0, 0.01, 0.03, 0.05, 0.1, 0.3, 0.5, 1.0) have been investigated. It was found that with increasing Co content, the Curie temperature decreases, while the spin glass transition temperature decreases first then increases. As for the sample with x = 0.3, the relation of and the merging point (for the zero-field-cooled and field-cooled magnetization curves starting to merge) with the applied magnetic field H follows a relation , ), where and are constants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
3
15
0
Order By: Relevance
“…via Jahn-Teller effects and large Hund's coupling effect that optimizes the electronic kinetic energy by the formation of ferromagnetic phase. However, it has been found that factors such as the average size of the cations, vacancies at La and Mn-sites and the oxygen stoichiometry also plays a crucial role in electrical and magnetic properties of manganite materials [11][12][13][14]. The key query is that are the monovalent-doped manganites fulfill the criterions set for divalent-doped manganites.…”
Section: Introductionmentioning
confidence: 99%
“…via Jahn-Teller effects and large Hund's coupling effect that optimizes the electronic kinetic energy by the formation of ferromagnetic phase. However, it has been found that factors such as the average size of the cations, vacancies at La and Mn-sites and the oxygen stoichiometry also plays a crucial role in electrical and magnetic properties of manganite materials [11][12][13][14]. The key query is that are the monovalent-doped manganites fulfill the criterions set for divalent-doped manganites.…”
Section: Introductionmentioning
confidence: 99%
“…Tel. : +86 10 62521523; fax: +86 10 62517887. substitution by various other ions such as Al [14,15], or transition metals Cr [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], Fe [18,20,[31][32][33][34][35][36][37][38][39][40][41], Co [20,25,[42][43][44][45][46][47][48], Ni [20,37,[49][50][51][52][53], Cu [20,[54][55][56][57][5...…”
Section: Introductionmentioning
confidence: 99%
“…Indications of such a transition have already been reported for CMR compounds, but without presenting convincing experimental evidences for its existence. Usually, the authors consider that a low temperature cusp in the zero-field-cooled (ZFC) magnetisation, leading to a difference between the ZFC and field cooled (FC) magnetisation curves at low temperatures, is enough to evidence a low temperature RSG phase [6][7][8][9]. Ac-susceptibility measurements are sometimes added; a frequency dependent ac-susceptibility is then attributed to the RSG phase [10][11][12].…”
mentioning
confidence: 99%